Analysis of geomagnetically induced currents (GIC) at equatorial region over solar cycle 24 / Zatul Iffah Abd Latiff and Mohamad Huzaimy Jusoh - Abd Latiff, Zatul Iffah; Jusoh, Mohamad Huzaimy (Universiti Teknologi MARA, 2021)
Geomagnetically induced currents (GIC) are one of the ground-end embodiment correlated with space environment perturbations owing to the Sun-Earth system's electromagnetic coupling. This natural hazard has contributed to the collapse of the global power grid, particularly during an extreme geomagnetic storm. For this study, global geomagnetic field data for equatorial regions focused on 9 extreme geomagnetic storms during solar cycle 24 were examined to explore the trend of GIC-related events centered on the temporal variations of horizontal element of geomagnetic field (dH/dt). The findings showed that there is a growing increase in the level of GIC as geomagnetic latitude (MLAT) crosses dip equator (±3°) due to Equatorial Electrojet (EEJ) Intensification. In equatorial region, a large number of extreme GIC events are also found to have occurred over day side. From the correlation study carried out between the Solar Wind (SW) parameter and the GIC activities, it can be inferred that the GIC activities at the equatorial region during solar cycle 24 indicate a strong dependency on solar wind input energy (ε Parameter) and solar wind dynamic pressure (Pdyn parameter). In contrast, the Interplanetary Magnetic Field (IMF) Bz component parameter exhibits the least dependency relationship.